Defective Severe Acute Respiratory Syndrome Coronavirus 2 Immune Responses in an Immunocompromised Individual With Prolonged Viral Replication. (2nd August 2021) - Gordon, Claire L; Smibert, Olivia C; Holmes, Natasha E; Chua, Kyra Y L; Rose, Morgan; Drewett, George; James, Fiona; Mouhtouris, Effie; Nguyen, Thi H O; Zhang, Wuji; Kedzierski, Lukasz; Rowntree, Louise C; et al.
Abstract: We describe severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–specific immune responses in a patient with lymphoma and recent programmed death 1 (PD-1) inhibitor therapy with late onset of severe coronavirus disease 2019 disease and prolonged SARS-CoV-2 replication, in comparison to age-matched and immunocompromised controls. High levels of HLA-DR + /CD38 + activation, interleukin 6, and interleukin 18 in the absence of B cells and PD-1 expression was observed. SARS-CoV-2–specific antibody responses were absent and SARS-CoV-2–specific T cells were minimally detected. This case highlights challenges in managing immunocompromised hosts who may fail to mount effective virus-specific immune responses. Abstract : We describe defects in severe acute respiratory syndrome coronavirus 2–specific immune responses and persistent viral replication in a patient with lymphoma. This case highlights challenges in managing immunocompromised hosts who may fail to mount effective virus-specific immune responses.